Different UV-B exposure times induce phenotypic, transcriptomic, and proteomic changes in wine grape leaves - Su Li; Yue Zhao; Qingyang Sun; Yifan Zhu; Xiahong He (Plant Stress, 2023)
The Shangri-La region, located in southwest China, is known for its dry climate and intense UltraViolet (UV) radiation due to its high altitude. Research conducted in the past has demonstrated that UV radiation, particularly UV-B radiation, enhances plants' ability to withstand cold temperatures, diseases, and arid conditions. Indeed, the Cabernet Sauvignon grape variety, predominantly cultivated in Shangri-La where the UV intensity reaches 21–22w/m2, has displayed remarkable resilience in recent decades. However, the specific impact of UV-B radiation on Cabernet Sauvignon grape leaves has yet to be fully understood. Consequently, our objective is to investigate the influence of UV radiation on grapes grown at high altitudes. To gain insights into the short-term effects on grape leaves, we conducted a comprehensive investigation involving anatomical and photosynthetic changes. Additionally, we analyzed the transcriptomic and proteomic regulation associated with these changes following exposure to UV-B radiation at intensities ranging from 15–20w/m2 for durations of 3 and 7 days.The findings of our study demonstrated that exposure to UV-B radiation, particularly at intensities surpassing 10w/m2, led to noticeable changes in the morphology of epidermal and palisade tissue cells. Furthermore, after a 3-day exposure to UV-B, we observed an upregulation of proteins responsible for cytoskeletal organization and cell wall synthesis. Conversely, following a 7-day treatment, proteins associated with disease resistance and antioxidants showed increased expression. Transcriptomic analysis revealed a significant enrichment of proteins and genes linked to pathogen infection, defense mechanisms, and antioxidant processes. Overall, our research highlighted the positive impact of intense UV radiation at high altitudes on enhancing disease resistance and environmental adaptability in Cabernet Sauvignon grape plants.